The Need for More Attention to Jubilee in Daniel 9:24–27 - Ulrich, Dean R. (Bulletin for biblical research, 2016)
Widely different readings of the prophecy of the 70 sevens in Dan 9 may exist, but the theme of Jubilee that is inherent in the prophecy's structure has received insufficient emphasis. In particular, previous scholarship has neglected (1) the relationship between the six objectives of Dan 9:24 and the details of Dan 9:25–27 and (2) the relationship between the Antiochene crisis and Jubilee theology. By reviewing previous scholarship on the 70 sevens, this article demonstrates that more work still needs to be done on this controversial passage.